Treatment of colorectal cancer by traditional Chinese medicine: prevention and treatment mechanisms - Sun, Jiaxin; Wei, Ying; Wang, Jia; Hou, Mingxing; Su, Liya (Frontiers in Pharmacology, 2024)
Colorectal cancer (CRC) is a significant global health burden, with high morbidity and mortality rates. It is often diagnosed at middle to advanced stage, affecting approximately 35% of patients at the time of diagnosis. Currently, chemotherapy has been used to improve patient prognosis and increase overall survival. However, chemotherapy can also have cytotoxic effects and lead to adverse reactions, such as inhibiting bone marrow hematopoiesis, causing digestive dysfunction, hand-foot syndrome, and even life-threatening conditions. In response to these adverse effects, researchers have proposed using Traditional Chinese Medicine (TCM) as an option to treat cancer. TCM research focuses on prescriptions, herbs, and components, which form essential components of the current research in Chinese medicine. The study and implementation of TCM prescriptions and herbs demonstrate its distinctive holistic approach to therapy, characterized by applying multicomponent and multi-target treatment. TMC components have advantages in developing new drugs as they consist of single ingredients, require smaller medication dosages, have a precise measure of pharmacodynamic effects, and have a clear mechanism of action compared to TCM prescriptions and herbs. However, further research is still needed to determine whether TMC components can fully substitute the therapeutic efficacy of TCM prescriptions. This paper presents a comprehensive analysis of the research advancements made in TCM prescriptions, herbs, and components. The findings of this study can serve as a theoretical basis for researchers who are interested in exploring the potential of TCM for the treatment of colorectal cancer.